Community Health Workers: Addressing Client Objectives Among Frequent Emergency Department Users - Kwan, Bethany M. (J Public Health Manag Pract, 2018)
OBJECTIVES: To evaluate effectiveness of a community health worker (CHW) program designed to address client objectives among frequent emergency department (ED) users. DESIGN: Program evaluation using secondary analysis of client objectives from program records. Client objectives were characterized according to the World Health Organization's social determinants of health framework. Hierarchical generalized linear modeling was used to assess factors associated with objective achievement. SETTING: An ED and the surrounding community in an economically disadvantaged area of Buffalo, New York. PARTICIPANTS: A total of 1600 adults over age 18 eligible for Medicaid and/or Medicare and who had at least 2 ED visits in the prior year. INTERVENTION: Clients worked with CHWs in the community to identify diverse needs and objectives. Community health workers provided individualized services to help achieve objectives. MAIN OUTCOME MEASURE: Achievement of client-focused objectives. RESULTS: Most objectives pertained to linkage to community resources and health care navigation, emphasizing chronic medical conditions and connection to primary care. Clients and CHWs together achieved 43% of total objectives. Objective achievement was positively associated with greater client engagement in CHW services. CONCLUSIONS: Low objective achievement may stem from system- and policy-level barriers, such as lack of affordable housing and access to primary care. Strategies for improving client engagement in CHW services are needed. Community health workers and their clients were most successful in areas in which public health policies and systems made resources easy to access or where the program had formalized relationships with resources, such as primary care.